TRADISI TARI GENDONG PADA MASYARAKAT SUKU ASLI ANAK RAWA KAMPUNG PENYENGAT KECAMATAN SUNGAI APIT KABUPATEN SIAK - Citra, Delima; Isjoni, Isjoni; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Tradition is custom which is done by a group of society passed down from generation to generation from generation and still tradition which done by society of Penyengat. The tradition of dance carrying is a dance as a form of expression of local people to give honor and worship to the spirits of the ancestors to avoid the catastrophes that will happen. This study aims, (1) To know the history of the tradition of dance carrying on the community of Anak Rawa native Siak district, (2) To know the factors that encourage the community of Anak Rawa still perform the traditional dance tradition of Siung District Penyengat Village (3) ) To find out the function of the traditional dance tradition in the community of Orang Asli Rawa Penyengat village of Siak district, (4) To know the process of carrying out the traditional dance tradition of the people penyengat children of Rawa Penyengat village Siak district, (5) To know the development of dance tradition in the community Suku Asli Anak Swamp Penyengat village Siak district. The benefits of research (1) As a scientific contribution for the library of FKIP in general and the Library of History Education Program in particular, (2) To deepen the science, especially for writers themselves in the field of research, (3) So also with the general public and for the younger generation to can love, learn the traditions of local art and introduce it to the world to keep the tradition sustainable. In this research using qualitative research method. Qualitative is a method that does not use numbers in data collection and in giving interpretation of results. The results of this study show that the tradition of Gendong Dance is one of the Tradition of Rawa native Tribe that is full of meaning and is a form of dance worship of ancestral spirits performed in big events by the people of Penyengat.Keywords: Tradition, Dance Saw